ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG DI KABUPATEN KUPANG (Analysis of factors that influence corn yield in Kabupaten Kupang) - Ade Darmawan Effendi; Suprapti Supardi; Kusnandar - (Universitas Muhammadiyah Semarang, 2017)
Agriculture sector is the main sector in Indonesia that can be made as one of economic growth sources. One of the commodities that can be utilized is corn. Corn (Zea mays) is the staple and substitutive food sources of the people of Nusa Tenggara Timur (NTT) however, the corn cultivation in NTT is not optimal because the corns are still planted traditionally. Many kinds of effort have been done in order to raise the corn yield in NTT. The aim of this research is to see the influence of the input variable and which input variable is the most dominant toward the corn yield. This research was held in six villages on three subdistricts in Kupang regency which was selected purposively, they were Fatuleu subdistrict, Taebenu subdistrict, and North Amfoang subdistrict. The number of farmers chosen as sample members from each subdistricts was 30.The data were collected through interview, observation, and questionnaire. In order to know the factors influencing the corn yield, the researcher used Cobb Douglas production function model.The result of the regression analysis showed that there were influence of the input variable toward the corn yield and the most dominant factors were the number of plants, pesticide, andnitrogen. The Cobb Douglas production function that was obtained was Y = (-576.723) - 301,801 X1 + 77,297 X2 + 0, 036 X3 + 5,437 X4 + 47,170 X5 + 31,095 X6 17,760 X7 +412,998 X8 + e.Keywords: Corn yield, Kupang regency, Cobb Douglas